Innovative Priority Mechanisms in Service Operations Theory and Applications - Cui, Shiliang (SpringerBriefs in Service Science, 2023)
This book introduces the most advanced and recent theoretical research on innovative priority mechanisms in service settings. It covers cutting-edge topics on service innovations such as line-sitting, service-position-trading, referral priority programs, queue-scalping, distance-based priority, and dynamic priority policy. It also contains a variety of practical examples and applications which help managers to make better decisions and to develop a coherent business strategy. This book appeals to a wide readership, from academics and Ph.D. students who are interested in priority mechanisms, to service managers and researchers in the service industry. This is an open access book.